In-depth genome and comparative genome analysis of a metal-resistant environmental isolate Pseudomonas aeruginosa S-8 - Kumari, Kiran; Sinha, Ayushi; Sharma, Parva Kumar; Singh, Rajnish Prakash (Frontiers in Cellular and Infection Microbiology, 2025)
The present study aimed to identify the mechanisms underlying the survival of an environmental bacterium originally isolated from the waste-contaminated soil of Jhiri, Ranchi, India. Based on 16S rRNA, ANI (average nucleotide identity), and BLAST Ring Image Generator (BRIG) analysis, the isolated strain was identified as Pseudomonas aeruginosa. The present study extends the characterization of this bacterium through genomic and comparative genomic analysis to understand the genomic features pertaining to survival in stressed environments. The sequencing of the bacterium at Illumina HiSeq platform revealed that it possessed a 6.8 Mb circular chromosome with 65.9% GC content and 63 RNAs sequence. The genome also harbored several genes associated to plant growth promotion i.e. phytohormone and siderophore production, phosphate solubilization, motility, and biofilm formation, etc. The genomic analysis with online tools unraveled the various genes belonging to the bacterial secretion system, antibiotic resistance, virulence, and efflux pumps, etc. The presence of biosynthetic gene clusters (BCGs) indicated that large numbers of genes were associated to non-ribosomal synthesized peptide synthetase, polyketide synthetase, and other secondary metabolite production. Additionally, its genomes encode various CAZymes such as glycoside hydrolases and other genes associated with lignocellulose breakdown, suggesting that strain S-8 have strong biomass degradation potential. Furthermore, pan-genome analysis based on a comparison of whole genomes showed that core genome represented the largest part of the gene pools. Therefore, genome and comparative genome analysis of Pseudomonas strains is valuable for understanding the mechanism of resistance to metal stress, genome evolution, HGT events, and therefore, opens a new perspective to exploit a newly isolated bacterium for biotechnological applications.